Forest census and map data for two temperate deciduous forest edge woodlot patches in Baltimore, Maryland, USA: Ecological Archives E096‐156. Issue 6 (1st June 2015) - Dandois, Jonathan P.; Nadwodny, Dana; Anderson, Erik; Bofto, Andrew; Baker, Matthew; Ellis, Erle C.
Abstract : This data set reports on a census of all trees within two 6.25‐ha plots (250 m × 250 m) of temperate deciduous woodlot patch on the campus of the University of Maryland Baltimore County (UMBC), Baltimore, Maryland, USA. Woodlot patches are primarily of the tulip poplar association. From 2011–2012, a 25 m × 25 m quadrat grid was established for each plot by total station surveying equipment. From 2012–2014, the location and DBH (diameter at breast height, 1.37 m) of all woody stems ≥ 1 cm DBH that reached ≥1.37 m tall were censused, whether living or dead. All such stems were also marked with numbered metal tags. All living stems were identified at least to genus and to species when possible. All censused stems and associated data (tag number, DBH, location, species, status) were entered into a geographic information system (GIS) map layer based on stem location within a Universal Transverse Mercator (UTM) projected coordinate system where each stem was represented as a unique point feature. The primary objective of these data is to provide a reference for stem location and diameter for the calibration and evaluation of ground‐based 3D remote sensing technologies based on computer vision and personal digital camera or cell phone image collections. With regular re‐census, the data could also be used for tracking growth, mortality, and recruitment of patchy forest woodlots within a suburban landscape mosaic.